Quizizz-enhanced biology learning: Improving junior high school students' mastery of bacterial concepts - Edi Sutomo; Rahmat Ramadansur; Raisa Anakotta; Tsukasa Hirashima (University of Muhammadiyah Malang, 2026)
Background: Delayed or non-diagnostic feedback for junior high school students in learning bacterial concepts can leave misconceptions uncorrected. Objectives: This study examined whether a teacher-mediated Quizizz-enhanced biology condition was associated with greater improvement in eighth-grade students’ mastery of bacterial concepts than the control class. Method: A quasi-experimental non-equivalent pretest-posttest control group design involved 88 students in two classes at SMP Negeri 11 Kabupaten Sorong, Southwest Papua, Indonesia. The experimental class learnt through teacher-guided instruction supported by Quizizz retrieval questions, immediate feedback, response review, and concept clarification. The control class was taught through explanation, slides, oral questioning, and written exercises. Individual N-gain scores were compared using Welch’s independent-samples t-test, supported by a Mann-Whitney U sensitivity analysis and Hedges’ g. Results: The experimental class achieved higher posttest than the control class in terms of mean values (i.e., 93.64 and 79.77) and N-gain values (.54 and .38). Significant improvement was gained by experimental class compared to the control one (t(74.51)=3.575, p<.001). Moreover, the sensitivity analysis supported these results (U=598.00, p=.002) with the standardized difference was g=.76. Conclusion: The integrated Quizizz-enhanced instructional cycle was associated with stronger improvement in bacterial concept mastery. The findings in this study represents a baseline-sensitive association rather than an isolated causal effect of the platform.